Unmasking Health and Inclusivity: Health Benefits of Traditional Indian Games for Children with Neurodevelopmental Disability - A Mansoor Rahman; Kavitha Raja; Muhammed Rashid (Journal of the Scientific Society)
Background: Physical activity plays a vital role in enhancing the health benefits and decreasing sedentary behaviors in children with neurodevelopmental disability. Adapted physical education by means of traditional games might have the potential to maximize the health benefits of children with neurodevelopmental disability. Objective: The objective of this study was to explore the value of traditional games in imparting health benefits in children with neurodevelopmental disability. Methodology: After a detailed review, the research paradigm has been framed to list and compile the traditional games of South India using Nisaratana Sangasubana framework to enhance health benefits for children with neurodevelopmental disability. Data Synthesis: The location of the data, the data-gathering, data-storage, data analysis (using modified Roper and Shapira strategies), and validation of data are done. Reflective Remarks: Finally, the list of traditional games which potentially have health benefits for children with neurodevelopmental disability has been obtained.